Analisis Penerapan Standar HACCP pada Dapur Produksi S’Best sebagai Upaya Menjaga Keamanan Konsumen - Natali Elasia Palis; Alicia Christina Mahar; Fricella Aprianda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Food safety is a critical aspect of food production, particularly for home-scale food businesses that often operate with limited formal control systems. The Hazard Analysis and Critical Control Point (HACCP) approach is widely recognized as an effective preventive system to identify, evaluate, and control potential food safety hazards. This study aims to analyze the implementation of HACCP principles in a home-scale pempek production unit, Dapur S’Best, as an effort to ensure food safety and consumer protection. This research employed a descriptive qualitative approach through direct observation and assessment using HACCP-based indicators. A total of 40 indicators covering raw material handling, processing stages, equipment sanitation, and hygiene practices were evaluated to identify potential hazards and critical control points during production. The results show that Dapur S’Best has implemented 35 out of 40 HACCP indicators, with an overall compliance level of 87.5%. The most critical stages identified were raw material reception and cooking processes, particularly in controlling biological hazards. These hazards were mitigated through the use of fresh raw materials, proper sanitation of equipment, and adequate cooking temperatures. Although HACCP has not been formally documented or certified, the production practices reflect a preventive approach consistent with HACCP principles. In conclusion, this study demonstrates that HACCP principles can be adaptively applied in home-scale food enterprises through simple and feasible practices. The findings contribute to food safety studies by highlighting the potential of HACCP-based approaches to enhance consumer protection and product quality in small-scale food businesses.